The Hells Gate and Backstairs Passage Ice Shelves, Victoria Land - Antarctica. - BARONI, CARLO (1988)
Marine specimens mixed with supraglacial debris occur at the southern margin of the Hells Gate ice shelf (HGIS), which covers an area of about 70 square kilometers. Shells and debris seem to derive from the grounding line of the ice shelf. They have been incorporated by bottom freezing and then transferred to the ablation surface of the HGIS, as pointed out by DEBENHAM (1920) for the McMurdo Ice Shelf. Several 14C dates have been obtained from shells mixed with supraglacial debris. The dates, uncalibrated, range from 1550 ± 175(GX- 14625) to 2780 ± 145 (GX- 14097) yr B.P. Topographical surveys and 14C datations were used to obtain preliminary values of some glaciological parameters of the HGIS (ice thickness, velocity, ice growth and ablation rates). The ice thickness of the southern part of the HGIS has been estimated at 63.5 m (eastern margin) and at 34.5 m (western margin). The latter is some 82 m 3 km inland from the same site. The mean surface velocity has been calculated to be 7.4 m yr", on the basis of the relative distances of the fossiliferous sites considered. The same parameter ranges from 10.4 m to 22.9 m yr! on the basis of the different source areas and of the various cal AD ages of the shells collected. The surface velocity has been estimated at about 3 m yr! at the eastern margin of the HGIS. The ice growth rate has been estimated at 12.2/25 em yr! at the western side of the ice shelf. A minimum rate of about 5 ern yr-1 has been valued at Hells Gate East. The ablation rate has been estimated only at Hells Gate West, where it ranges from 16.5 ern to 36.3 em yr! considering the ice lost in the last 3 km, on the basis of the difference between the calculated thickness of the HGIS with respect to different velocity values. A minimum value for the same parameter ranges from about 5 em to 23.6 em yr ", considering the ice lost, as recorded by height of the dirt cones above the HGIS surface. On the basis of qualitative observations, the occurrence of a calving margin has also been verified for the HGIS. ...